Towards an aesthetics of grammar learning: lifting the veil on language - Ainsworth, Steph; Bell, Huw (Frontiers in Education, 2024)
The last few decades have seen growing interest in the field of disciplinary aesthetics. While the physical sciences and mathematics have attracted significant interest in this area, relatively little attention has been given to the aesthetic potential of learning about the structure of one’s own native language. Within this paper, we bring together ideas from evolutionary aesthetics, philosophy, psychology and neuroscience to explore the question of what might characterise an aesthetics of grammar learning. The paper connects our previous empirical findings with theoretical developments across these disciplines. We argue that explicit grammar learning has a particular potential to evoke aesthetic experience due to its role as a mediator between procedural and declarative knowledge. We suggest that by facilitating the transformation from knowhow to knowledge, grammar learning has the potential to generate cognitive consonance, experienced as an aesthetic-epistemic feeling of fittingness. The discussion draws parallels between the characteristics of grammar and the properties of entities more traditionally conceived to be aesthetic (such as art works and performances). In particular, we note that meta-linguistic labels (grammar terms) provide concrete tokens which facilitate virtual models, supporting the transition from ‘automatism’ to ‘conscious reflection’. The paper concludes by exploring the implications for the field of disciplinary aesthetics and for developing pedagogies which maximise the aesthetic potential of grammar.